2018
DOI: 10.1002/pc.24890
|View full text |Cite
|
Sign up to set email alerts
|

Static, dynamic mechanical and thermal properties of untreated and alkali treated mulberry fiber reinforced polyester composites

Abstract: In this research work, the untreated and various concentrations of alkali treated continuous mulberry fibers were used as reinforcement in polyester matrix and its static and dynamic mechanical properties were investigated. The composites were fabricated using untreated, 5%, 10%, and 15% alkali treated mulberry fibers (ATMF) reinforced in polyester resin by compression molding technique. The result showed that the 10% alkali treated mulberry fiber composite (ATMFC) considerable increase in tensile, flexural, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 43 publications
(52 reference statements)
3
36
0
Order By: Relevance
“…The alkali treatment removes the hydroxyl ions from the cell wall of cupula fibers resulted in increased rougher surface and deeper pores. This provides obtaining the mechanical properties and increasing the amount of cellulose exposed on the alkali treated fiber surface resulted in the number of possible reaction sites . The surface of the alkali treated cupula fiber added composite had coarser than compared to untreated cupula fiber as reported in some researches …”
Section: Resultsmentioning
confidence: 86%
“…The alkali treatment removes the hydroxyl ions from the cell wall of cupula fibers resulted in increased rougher surface and deeper pores. This provides obtaining the mechanical properties and increasing the amount of cellulose exposed on the alkali treated fiber surface resulted in the number of possible reaction sites . The surface of the alkali treated cupula fiber added composite had coarser than compared to untreated cupula fiber as reported in some researches …”
Section: Resultsmentioning
confidence: 86%
“…All the composites were brittle. This may be due to agglomeration of the sand particles and reduction in the interfacial bonding between matrix and sand [26].…”
Section: Tensile Properties Of the Compositesmentioning
confidence: 99%
“…Libo Yan et al [ 16 ] also reported that 5% alkali treatment makes the coir fiber surface clear, rough, and also improves the strength of the polymer composites. Shanmugasundaram et al [ 33 ] studied the effect of alkali treatment (5%, 10%, 15%) on the physical, thermal, mechanical, and chemical properties of Areca palm leaf stalk fiber and they concluded that alkali treatment removes the hemicellulose and waxy substances from the fibers whereas the 5% alkali‐treated fibers showed improvement in the mechanical properties of the polymer composites. Among different types of surface treatments, NaOH treatment was most commonly used for enhancing the compatibility of natural fibers with the matrix.…”
Section: Introductionmentioning
confidence: 99%